2016
DOI: 10.1097/hjh.0000000000000780
|View full text |Cite
|
Sign up to set email alerts
|

Serum bisphenol A as a predictor of chronic kidney disease progression in primary hypertension

Abstract: Serum BPA may be a predictor of CKD progression in patients with primary hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 32 publications
0
33
1
Order By: Relevance
“…Although renal excretion is another important aspect of uric acid metabolism, the urinary uric acid excretion seemed not to be influenced by BPA. We reported in earlier work that BPA is a predictor of 6 yr chronic kidney disease progression in patients with primary hypertension (11) and type 2 diabetes (22). Experimental studies also showed that BPA exposure promotes podocytopenia and proteinuria (39).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Although renal excretion is another important aspect of uric acid metabolism, the urinary uric acid excretion seemed not to be influenced by BPA. We reported in earlier work that BPA is a predictor of 6 yr chronic kidney disease progression in patients with primary hypertension (11) and type 2 diabetes (22). Experimental studies also showed that BPA exposure promotes podocytopenia and proteinuria (39).…”
Section: Discussionmentioning
confidence: 98%
“…Apart from this, it should be noted that uric acid clearance does not decrease in proportion to the glomerular filtration rate in chronic kidney disease (40). Even though exposure of BPA decreases the glomerular filtration rate, the compensatory increase in uric acid excretion per nephron may help to maintain a normal level of uric acid clearance (11, 23, 39, 40).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The likely mechanism involves the ability of BPA to disrupt normal estrogen-ER signaling in the vasculature, which normally affords vascular protection by promoting vascular injury repair and upregulation of vasodilators such as nitric oxide. Finally, it has recently been suggested that serum BPA levels could be used to predict the progression of chronic kidney disease in hypertensive individuals [200].…”
Section: Cardiovascular Diseasementioning
confidence: 99%